Experimental extraction of secure correlations from a noisy private state. - Dobek, K; Karpiński, M; Demkowicz-Dobrzański, R; Banaszek, K; Horodecki, P (2011)
We report experimental generation of a noisy entangled four-photon state that exhibits a separation between the secure key contents and distillable entanglement, a hallmark feature of the recently established quantum theory of private states. The privacy analysis, based on the full tomographic reconstruction of the prepared state, is utilized in a proof-of-principle key generation. The inferiority of distillation-based strategies to extract the key is exposed by an implementation of an entanglement distillation protocol for the produced state.